Influence of the value of CCS and CBT on the final value paid per liter of milk (Research, Society and Development, 2021)
This study aimed to evaluate the effect of penalties or bonuses related to total bacterial count (TBC) and somatic cell cout (CCS) of milk on the final amount paid for liter of milk in a property in Minas Gerais. Monthly data were collected regarding the CBT and CCS values obtained after analyzing the milk and the information regarding the amount paid per liter, delivered between the months of October 2019 to June 2020. Of the 9 months analyzed, the property did not show changes in the CBT value, remaining with na overall average of 7 (x1000) UFC/ml, remaining below the average required by IN 76, which allows a maximum value of 300(x1000) CFU/ml. The producer received a subsidy with R$ 0.04 per liter, raising at the end of the period an amount of R$ 1,877.00. The mean value of CCS in the study period was 464.3(x1000) CS/ml, however the analyzes from October 2019 to February 2020 showed an increase in the CCS value, resulting in an average of 576.2(x1000) CS/ml, remaining outside from maximum standards required by IN 76 of 500(x1000) CS/ml, resulting in a penalty to the producer of R$ 0.06 per liter. The penalty reflected in a 5% reduction in the final amount paid for the liter of milk. After the adoption of corrective and preventive practices, there was a reduction in the value of the farm’s CCS. Thus, it is possible to conclude that technical assistance is of paramount importance to advise the producesr on the best development of the dairy activity, maximizing the property’s financial return.